Smoothening Perfluoroalkylated Surfaces: Liquid‐Like Despite Molecular Rigidity? - Parham Koochak; Mariia S. Kiseleva; Sakari Lepikko; Mika Latikka; Robin H. A. Ras; William S. Y. Wong (Advanced Materials Interfaces)
Abstract The rational design of surfaces at the molecular level is essential toward realizing many engineering applications. However, molecular‐scale defects affect processes such as triboelectrification, scaling, and condensation. These defects are often detectable via contact angle hysteresis (CAH) measurements. Liquid‐like surfaces exhibit extremely low CAH (≤5°) and rely on the use of highly flexible molecular species such as long‐chain alkyls or siloxanes. Their low glass transition temperatures lead to the so‐termed self‐smoothing behavior, reducing sensitivity to defects formed during fabrication. However, utilizing rigid molecular species such as perfluoroalkyl chains often results in higher hysteresis (10° to 60°) as defects are not self‐smoothed after fabrication. Consequently, state‐of‐the‐art perfluoroalkylated surfaces often show sub‐optimal interfacial properties. Here, a customizable chemical vapor deposition process creates molecularly‐thick, low‐defect surfaces from trichloro(1H,1H,2H,2H‐perfluorooctyl)silane. By implementing moisture‐exposure controls, highly homogenous surfaces with root‐mean‐square roughness below 1 nm are fabricated. CAH is achieved down to ≈4° (average: 6°), surpassing the state‐of‐the‐art by ≈5°. Reduction of CAH (26° to 6°) results in condensation suppression, decreasing surface droplet density by one order and surface droplet coverage by 40%. This work guides the synthesis of high‐quality surfaces from tri‐functional perfluoroalkylsilanes with liquid‐like properties despite their molecular rigidity.